Boundary value problems for mixed-type equationsinvolving the Bessel operator of fractional order - Yunusaliyeva Mohinur To'lqinjonovna (Periodica Journal, 2025)
This article is devoted to the study of boundary value problems for mixed-type equations involving the Bessel operator of fractional order. The research focuses on the formulation, analysis, and solution of such equations, which play a significant role in various mathematical and physical applications. The properties of the Bessel operator and its influence on the behavior of solutions are examined in detail. Methods for solving these boundary value problems are proposed, and their effectiveness is demonstrated through examples
Keywords: mixed-type equations; Bessel operator; fractional order